Influence of internal organizational factors and institutional pressures on construction firms’ performance - Fehan, H.; Aigbogun, Osaro (2021)
A significant number of empirical studies have reported contrasting results regarding the effects of certain internal organizational factors (Leadership Style - Team competency and Skills - Effective Communication) on construction performance. As a result, generalizations remain sketchy, and a better understanding is needed. This study lends a voice to the literature’s debate by introducing the part played by institutional pressures. The aim is to evaluate the impact of internal organizational factors and institutional pressures on a Syrian construction firm’s performance outcomes, with institutional pressures playing a mediator’s role. Data were collected using a questionnaire instrument from a sample of 197 building experts working in large public construction companies in Syria and analysed using the partial least squares structural equation modelling (PLS-SEM). The results reveal that leadership style and effective communication have a significant and positive effect on construction firm performance outcomes. However, the effect of team competency and skill was not supported; nonetheless, providing institutional pressures as a mediator into the relationship made it significant, thus, providing a vital theoretical contribution worth considering in future research. Practically, this study is the first attempt at evaluating organizational factors and institutional pressures as a critical determinant of organizational performance that should interest management at organizational levels.